Implementation of Classical Guidance at SMP Bina Satria Medan - Prasetyo, Wahyu (Universitas Dharmawangsa, 2022)
The purpose of this study is to find out: 1) How is the implementation of classical guidance at SMP Bina Satria Medan; 2) What are the obstacles encountered in implementing classical guidance at Bina Satria Middle School Medan; 3) What are the results achieved in the implementation of classical guidance at SMP Bina Satria Medan. The type of research used is a type of qualitative research with field research methods. Data collection techniques are interviews, observation and documentation. Furthermore, the analysis technique used is an inductive qualitative data analysis technique. The results of this study are the implementation of classical guidance at SMP Bina Satria Medan, namely the implementation of classical guidance at SMP Bina Satria Medan does not have special hours; the tools used are in the form of AUM and LKPD questionnaires; its implementation has not been carried out routinely, its implementation includes the initial, core and closing stages; the material used comes from the internet, books and training; The method used is the lecture method, discussion and question and answer. Obstacles experienced in the implementation of classical guidance include the lack of interest in student learning in following classical guidance; inadequate time in implementing classical guidance; lack of active counseling staff in the implementation of classical guidance. The results achieved in the implementation of classical guidance are the achievement of guidance goals for students; evaluation of students after carrying out classical guidance with evaluation of processes and results.